Response of Root Exudates of Bruguiera gymnorrhiza (L.) to Exposure of Polycyclic Aromatic Hydrocarbons - Liu, Beibei; Wu, Lin; Pan, Pan; Li, Ruilong; Lin, Bigui (Frontiers in Environmental Science, 2022)
Root exudates play a pivotal role in the behaviors of polycyclic aromatic hydrocarbons (PAHs) in mangrove sediments, but the knowledge of how mangrove root exudates response to PAHs pollutants is limited. This study examined the root exudates of Bruguiera gymnorrhiza (L.) (B. gymnorrhiza) under exposure in phenanthrene, pyrene, and benzo[a]pyrene solution through a 45 days hydroponic cultivation. The results showed that the root exudates of B. gymnorrhiza were mainly hydrocarbon compounds. Tartaric acid was the dominant low molecular weight organic acids (LMWOAs) in root exudates. Under PAHs stress, the proportion of hydrocarbon compounds in root exudates decreased, while the proportion of amide compounds increased. At the first 15 days exposure, the amounts of dissolved organic carbon, soluble total sugars, total organic acids and LWMOAs all increased and reached the maximum values, subsequently, the amounts of root exudates had dropped. The degradation rates of PAHs followed the sequence of phenanthrene > pyrene > benzo [a] pyrene, and the presence of root exudates can significantly enhance the degradation of PAHs. The results illustrated that PAHs stress can significantly change the concentrations and species of root exudates. This study provides the scientific reference for understanding the ability of B. gymnorrhiza response to PAHs stress.